1,3,4-Oxadiazole Contained Sesquiterpene Derivatives: Synthesis and Microbiocidal Activity for Plant Disease - Dai, Ali; Zheng, Zhiguo; Yu, Lijiao; Huang, Yuanqin; Wu, Jian (Frontiers in Chemistry, 2022)
A series of 1,3,4-oxadiazole contained sesquiterpene derivatives were synthesized, and the activity of the target compounds against Xanthomonas oryzae pv. oryzae (Xoo), Xanthomonas axonopodis pv. citri (Xac), and tobacco mosaic virus (TMV) were evaluated. The biological activity results showed that the EC50 values of compounds H4, H8, H11, H12, H14, H16, and H19 for Xac inhibitory activity were 33.3, 42.7, 56.1, 74.5, 37.8, 43.8, and 38.4 μg/ml, respectively. Compounds H4, H8, H15, H19, H22, and H23 had inhibitory effects on Xoo, with EC50 values of 51.0, 43.3, 43.4, 50.5, 74.6, and 51.4 μg/ml, respectively. In particular, the curative and protective activities of compound H8 against Xoo in vivo were 51.9 and 49.3%, respectively. In addition, the EC50 values of the inactivation activity of compounds H4, H5, H9, H10, and H16 against TMV were 69.6, 58.9, 69.4, 43.9, and 60.5 μg/ml, respectively. The results of molecular docking indicated that compound H10 exhibited a strong affinity for TMV-coat protein, with a binding energy of −8.88 kcal/mol. It may inhibit the self-assembly and replication of TMV particles and have an anti-TMV effect, which supports its potential usefulness as an antiviral agent.